Characterization and phenological prediction of tropical black bean genotypes - Inurreta-Aguirre, Héctor Daniel; Tosquy-Valle, Oscar Hugo; Rodríguez-Moreno, Víctor Manuel; Ibarra-Perez, Francisco Javier; Zetina-Lezama, Rigoberto (Revista Mexicana de Ciencias Agrícolas, 2026)
The phenological characterization of black bean varieties generated by the Bean Program of the National Institute of Forestry, Agricultural and Livestock Research for southeastern Mexico is conducted by quantifying the number of days after sowing required to reach the different stages of development. This characterization is imprecise for contrasting environments. This study aimed to characterize nine advanced lines and two varieties of opaque black beans by using the number of days after sowing and the index of growing degree-days necessary to achieve the stages of flowering and physiological maturity and to compare the accuracy of the number of days after sowing and the growing degree-days to predict phenology. The number of days after sowing and the growing degree-days required by the genotypes to reach the flowering and physiological maturity stages were quantified across nine environments in southeastern Mexico. The ability of five mixed models was evaluated, considering the number of days after sowing, growing degree-days and environment as fixed effects and genotype as a random effect, to predict the phenological stages of the lines and varieties. Four lines were earlier than Negro Grijalva (1 892 growing degree-days), with an average of 1 859 growing degree-days; in contrast, four others obtained an average of 1 902 growing degree-days, higher than Negro Grijalva but lower than Negro Comapa (1 920 growing degree-days) and only one line was later than both varieties (1 976 growing degree-days). The best model for predicting phenology was the one that considered only the growing degree-days, regardless of the environment. It was concluded that growing degree-days are more accurate than the number of days after sowing for predicting the flowering and physiological maturity of the genotypes in the different evaluation environments.